Regimes de sentido e interação do K-POP na projeção da Coreia do Sul no Ocidente - Moura, Valeska Amaral de (2023)
This research aims to study the sense and interaction regimes used by South Korea for its projection in the Western using K-Pop. As the musical genre industry in the country gained worldwide prominence, what paths did the government take to make it possible? In the search for explanations of this phenomenon, the recent history of music on the Korean Peninsula will be explored since the establishment of the Republic of Korea and the years of development and structuring until the elaboration of the South Korean popular style, K-Pop, are pointed out. An analysis of the consequences that foreign domination impacted, in which these impacts allowed the absorption of different rhythms and adaptations, both musical and social, for the survival of the country's artists in difficult times. It is also analyzed what these interventions caused in the South Korean music scene with the emergence of entertainment companies and what they developed in programming and adaptations to figuratively base their artists to create the idol, an artist programmed to do so. This research sought to elucidate the narrative path of the idol, in addition to the pathemic impacts caused by these bodies in the making-to-be. As a corpus of this research, the BTS group was selected, they are currently one of the biggest groups in the music scene, not only in South Korea but also in the world, their narrative journey in the industry in three different eras, No More Dream (2013), Blood, Sweat & Tears (2016) and Dynamite (2020), as well as the thematic role of the members not only in act, but in what makes the group unique and unites “The BTS”. The study is divided into two fronts, the first on the faces and bodies of the members of the group in relation to the euphoric or dysphoric impacts they cause, the adjustments were made based on these perceptions alongside with shaping the artists to attend to the needs of the industry. These changes range from diets and makeup to surgical intervention through the Concept Photos; the second analysis focuses on the performance with the songs, identifying the sender-target relationship and how it is presented. The theoretical foundation for description and analysis is from the semiotic theory of Algirdas Julien Greimas with the developments of Eric Landowski. The plastic semiotics of Jean-Marie Floch and Ana Claudia de Oliveira were used to analyze the faces, performance and body of the artists.The research contributes to the understanding of the regimes of senses and positive or negative interactions of a country through its global impact